INCREASING STUDENTS’ READING COMPREHENSION SKILL USING LITERATURE: CLASSROOM ACTION RESEARCH AT SMAN 1 PAITON - Qamariyah, Farihatul; Tirmidi, Tirmidi; Ningsih, Sholehatin (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to improve students' reading skills in literary texts by utilizing songs in the English learning process. This research uses Classroom Action Research following the Kemmis and McTaggart model, with four main phases: planning, implementation, observation, and reflection. This research was conducted at SMAN 1 Paiton, in the first semester of the 2025/2026 academic year with 32 students from class XII SMAN 1 Paiton as the research subjects. The learning process was carried out through two cycles using English songs. Data were obtained through observation, interviews, reading tests, and documentation. The research findings showed a significant improvement in students' reading skills, from an average score of 63.4 before the intervention to 74.1 in cycle I and 84.3 in cycle II. The learning pass rate increased from 0% to 90.6%. In addition, student participation and interest in reading activities also jumped to 87.5%.